Obesity and overweight in IMSS female workers in Mexico City Obesidad y sobrepeso en mujeres trabajadoras del IMSS, en la Ciudad de México - José Luis Vázquez-Martínez; Héctor Gómez-Dantés; Felipe Gómez-García; María de los Angeles Lara-Rodríguez; Joel Navarrete-Espinosa; Gabriela Pérez-Pérez (Instituto Nacional de Salud Pública, 2005)
OBJECTIVE: To estimate the prevalence and risk factors for overweight (OW) and obesity (OB) in women working at the Mexican Social Security Institute (IMSS, per its abbreviation in Spanish) in Mexico City, using two different classification criteria. MATERIAL AND METHODS: A cross-sectional study was performed from July 1999 to September 2000. It included 588 women 20 to 65 years of age and who were working at the IMSS. The criteria used to estimate the prevalence of OW and OB were the WHO criteria and the Mexican Official Norm (NOM) for the integrated management of obesity in Mexico. RESULTS: The frequency of OB, according to WHO criteria, was 27.6% (26% adjusted) and for OW 43.2% (40.2% adjusted). According to the NOM, the levels of OB in those with short height (<1.50 m) increased to 75% and to 52.2% for those with height >1.50 m. Comparison of BMI between the two height groups showed no differences. The risk factor associated with OB and OW was age. Education and exercise were protective factors. CONCLUSIONS: The high prevalences detected in this particular working group highlight the importance of prevention and control of OB in health personnel because it can result in a high number of disability and premature retirement due to disease. The use of the NOM criteria for the identification of women at risk may be useful for early detection of high-risk groups. OBJETIVO: Estimar la prevalencia de obesidad (OB) y sobrepeso (SP) en mujeres trabajadoras del IMSS en la Ciudad de México, aplicando dos criterios de clasificación y su asociación con algunos factores de riesgo. MATERIAL Y MÉTODOS: Estudio transversal realizado entre julio de 1999 y septiembre de 2000 que incluyó a 588 mujeres trabajadoras en el IMSS entre 20 y 65 años. Los criterios utilizados para medir la prevalencia de OB y SP fueron los propuestos por la OMS y la Norma Oficial Mexicana para el manejo integral de la obesidad (NOM). RESULTADOS: La frecuencia de OB fue 27.6% (26% ajustada) y de SP de 43.2% (40.2% ajustada) al aplicar los criterios de la OMS. Conforme a la NOM, los niveles de OB en el grupo de talla baja (<1.50 m) se elevaron a 75% y en el de talla mayor a 1.50 m a 52.2%. Sin embargo, al comparar el índice de masa corporal de talla baja y talla normal no se aprecian diferencias. El factor de riesgo para OB y SP fue la edad. En forma protectora resultaron la educación y el ejercicio. CONCLUSIONES: Las altas prevalencias de OB y SP en la población estudiada constituyen un riesgo importante para la salud de este grupo de población, que se puede traducir en altos niveles de discapacidad y pensiones con un alto costo para la Institución. Estos resultados demandan la realización de intervenciones que permitan identificar precozmente a mujeres con índices de masa corporal de riesgo. Los rangos propuestos por la NOM pueden ser de utilidad para la identificación precoz de las mujeres en riesgo.